Analisis Penerapan PSAP Nomor 13 Tentang Penyajian Laporan Keuangan Badan Layanan Umum Pada RSUP Prof. Dr. R. D. Kandou Manado - Kawenas, Riani Isye; Kalangi, Lintje; Lambey, Linda (Universitas Sam Ratulangi, 2018)
Abstract. This study aims to analyze the presentation of financial statements in public service agencies at the RSUP Prof. Dr. R. D. Kandou in accordance to PSAP Number 13. This is a qualitative exploratory research. Data were obtained by in-depth interviews, observation and documentation study. Key informants were determined by purposive sampling in order to meet criterias and to obtain accurate and correct information. Triangulation techniques were used to test the validity of data and data sources. The data were transcribed from the interviews transcriptions. The transcriptions were analyzed by analytical methods consisting of finding themes/coding, conceptualizing scientific statements and interpreting them in narrative form. The results show that the presentation of financial statements in public service agencies at the Prof. Dr. R. D. Kandou has implemented or in accordance to PSAP Number 13. However, they do not completely implement it, particularly in recognizing revenue on Operational Cooperation (KSO). In fact, there are some obstacles in preparing the financial statements. Those obstacles are (1) no clear regulation on the definition of KSO, (2) lack of additional rules or technical guidelines to describe the implementation of PSAP Number 13 for KSO, (3) lack of communication from the Ministry of Health to the Hospital resulting in lack of qualified human resources influences the realization target of PNBP and (4) the assessment of hospital performance is influenced by PSAP Number 13. Due to the importance of the work unit to comply with this regulation, it is necessary to strive to support policies to ensure the implementation of PSAP Number 13 is in accordance to the provisions.Keywords: PSAP Number 13, Public Service Board, Regulation, Effect of ImplementationAbstrak. Penelitian ini bertujuan menganalisis penyajian laporan keuangan badan layanan umum pada RSUP Prof. Dr. R. D. Kandou berdasarkan penerapan PSAP Nomor 13. Penelitian ini menggunakan metode kualitatif dengan pendekatan eksploratori. Data diperoleh melalui teknik wawancara mendalam, observasi dan studi dokumentasi. Informan kunci ditetapkan secara purposive sampling dengan memenuhi kriteria yang ditetapkan untuk mendapatkan informasi yang tepat dan akurat. Teknik triangulasi digunakan untuk menguji validitas data dan sumber data. Data transkrip yang diuraikan dari hasil wawancara dianalisis menggunakan metode analisis yang terdiri dari pemberian tema/coding, konseptualisasi pernyataan ilmiah dan menginterpretasikannya dalam bentuk narasi. Hasil penelitian menunjukkan bahwa penyajian laporan keuangan badan layanan umum pada RSUP Prof Dr. R. D. Kandou berdasarkan PSAP Nomor 13 telah diterapkan, namun belum secara keseluruhan, khususnya dalam mengakui pendapatan atas Kerjasama Operasional (KSO). Dalam penyusunan laporan keuangan masih ditemukan beberapa kendala antara lain (1) belum adanya regulasi yang jelas tentang pengertian KSO, (2) belum tersedianya aturan tambahan atau petunjuk teknis untuk menjabarkan penerapan PSAP Nomor 13 untuk KSO, (3) kurangnya komunikasi dari Kementerian Kesehatan RI kepada Rumah Sakit yang mengakibatkan kurangnya SDM yang memahami dan (4) adanya pengaruh penerapan PSAP Nomor 13 terhadap target realisasi PNBP pengaruh penerapan PSAP Nomor 13 pada penilaian kinerja Rumah Sakit.Â Karena pentingnya satuan kerja untuk patuh pada regulasi ini maka perlu diupayakan kebijakan pendukung untuk memastikan implementasi PSAP Nomor 13 berjalan sesuai ketentuan.Kata Kunci: PSAP Nomor 13, Badan Layanan Umum, Regulasi, Pengaruh Penerapan.